Low protease activity in B cell follicles promotes retention of intact antigens after immunization - Aung, Aereas; Cui, Ang; Maiorino, Laura; Amini, Ava; Gregory, Justin R.; Bukenya, Maurice; Zhang, Yiming; Lee, Heya; Cottrell, Christopher A.; Morgan, Duncan M.; Silva, Murillo; Suh, Heikyung; et al. (Science, 2023)
The structural integrity of vaccine antigens is critical to the generation of protective antibody responses, but the impact of protease activity on vaccination in vivo is poorly understood. We characterized protease activity in lymph nodes and found that antigens were rapidly degraded in the subcapsular sinus, paracortex, and interfollicular regions, whereas low protease activity and antigen degradation rates were detected in the vicinity of follicular dendritic cells (FDCs). Correlated with these findings, immunization regimens designed to target antigen to FDCs led to germinal centers dominantly targeting intact antigen, whereas traditional immunizations led to much weaker responses that equally targeted the intact immunogen and antigen breakdown products. Thus, spatially compartmentalized antigen proteolysis affects humoral immunity and can be exploited.